Corporate governance - a multi-theoretical approach to recognizing the wider influencing forces impacting on organizations - Christopher, Joseph (Academic Press, 2010)
It has been argued by researchers that agency theory has limitations as the underpinning theory for governance given its inability to recognize the wider environmental influencing forces impacting on organizations. This paper provides a case for incorporating a number of management-based theories to augment agency theory in recognizing these wider environmental influencing forces and the consequent extended governance paradigm it creates. Through a theory building approach that reviews and critically analyses the extant literature, a case is built to integrate four existing theories that complement each other to recognize these wider influencing forces. The paper argues that the proposed approach will narrow the theoretical practical gap in governance and will consequently have policy implications on governance guidelines. Further research is suggested to validate the approach with a wide range of real life organizational settings.